Effect of implantation and melengestrol acetate feeding on blood serum profiles and performance of heifers - Brandt, Robert T., Jr.; Milton, C.T.; Campbell, N.; Titgemeyer, Evan C. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Payout characteristics of Revalor-H and Finaplix-H were measured in 30 heifers (678 pounds) assigned to one of six treatments: 1) negative control, 2) melengestrol acetate (MGA) (.5 mg/hd/d), 3) Finaplix-Hfi, 4) Finaplix-H + MGA, 5) Revalor-Hfi, and 6) Revalor-H + MGA. Blood samples were collected by jugular puncture on days 0, 1, 3, 5, 7, 13, 21, 28, 42, 56, 84, 112, and 140. Following implantation with either Revalor-H or Finaplix-H, serum trenbolone (TB) increased markedly at 1 and 3 days after implantation, then decreased through day 42. A second peak in serum TB was observed on day 56. Between days 56 and 84, a drop in serum TB was observed. Although TB in heifers implanted with Revalor-H or Finaplix-H was lowest between 84 and 140 days, the observed TB may still have been adequate to modify heifer performance over this period of time. Average daily gain and feed efficiency demonstrated an implant MGA interaction. Heifers with no implant responded to MGA supplementation with increased rate of gain, whereas heifers receiving either Revalor-H or Finaplix-H had less weight gain when fed MGA.
Keywords: Beef; Implants; Heifers